A method to determine radial speed of target from FMCW radar signal - Sediono, Wahju (Radar and Communication Systems, 2008)
A well-known method to detect a target from FMCW radar signal is implemented using range FFT. By repeating the same procedure many times at a certain azimuth angle, one can additionally determine the radial speed of the suspected target. This work describes a simple method in determining the radial speed of target by extracting a series of phase data from the repeated range FFTs.